Advanced Design and Fabrication of Dual-Material Honeycombs for Improved Stiffness and Resilience - Jiajing Dong; Songtao Ying; Zhuohao Qiu; Xixi Bao; Chengyi Chu; Hao Chen; Jianjun Guo; Aihua Sun (Micromachines, 2023)
Auxetic re-entrant honeycomb (AREH) structures, consisting of a single soft or tough material, have long faced the challenge of balancing stiffness and rebound resilience. To achieve this balance, dual-material printing technology is employed to enhance shock absorption by combining layers of soft and tough materials. Additionally, a novel structure called the curved re-entrant honeycomb (CREH) structure has been introduced to improve stiffness. The selected materials for processing the composite structures of AREH and CREH are the rigid thermoplastic polymer polylactic acid (PLA) and the soft rubber material thermoplastic polyurethane (TPU), created utilizing fused deposition modeling (FDM) 3D printing technology. The influence of the material system and structure type on stress distribution and mechanical response was subsequently investigated. The results revealed that the dual-material printed structures demonstrated later entry into the densification phase compared to the single-material printed structures. Moreover, the soft material in the interlayer offered exceptional protection, thereby ensuring the overall integrity of the structure. These findings effectively serve as a reference for the design of dual-material re-entrant honeycombs.